PENDIDIKAN KARAKTER DALAM ISLAM : PERSPEKTIF PEMIKIRAN IBNU KHALDUN - Miftakkhul jannah; Ahmad Mustafidin (As-Sulthan Journal of Education, 2025)
Character education is an important issue in the context of modern Islamic education, which is confronted with various social, technological, and rapidly changing values. Ibn Khaldun, a 14th-century Muslim scholar, has relevant views on character education that can be applied in the context of modern Islamic education. This research utilizes a literature analysis method to understand Ibn Khaldun's views and concepts on character education. Data were collected from Ibn Khaldun's works related to education and character, such as "Muqaddimah" and other writings. The results of the analysis indicate that Ibn Khaldun considers character education as a crucial foundation for creating a quality society. Concepts such as ethics, social consciousness, leadership, and interpersonal skills are found in Ibn Khaldun's views on character education. This research discusses the relevance of Ibn Khaldun's views to the challenges of modern Islamic education. Through understanding Ibn Khaldun's concepts, modern Islamic education can face challenges by developing a curriculum that integrates character values, strengthens social awareness, trains leadership, and enhances students' interpersonal skills. This research contributes to theoretical and practical understanding in the field of character education and modern Islamic education. The findings of this research can provide guidance and guidance for educators, curriculum developers, and educational practitioners in addressing the challenges of modern Islamic education with an approach based on Ibn Khaldun's views on character education.